Contemporary Heritage Lexicon - Bartolomei, Cristiana,Ippolito, Alfonso,Vizioli, Simone Helena Tanoue (Springer Nature Switzerland, Imprint: Springer, 2024)
Zusammenfassung: This book presents themes related to contemporary architecture as the results of diverse cultural influences and architectural legacies, manifested in a rich variety of styles, materials, and spatial perceptions. It consists of 24 chapters written by authors from various continents and contains the result of research highlighting contemporary architecture in relation to multiple aspects that are distinguished by their eclectic nature, characterized by the integration of diverse cultural and architectural influences. The book examines aspects involving material aspects, technologies, design, history, salvage, technologies, and digitization. The aspects covered are always filtered through research, which objectively integrates traditional and innovative approaches. Thus, the focus is to explore the contemporary lexicon not only in the field of architecture and engineering, but in all those areas where this theme can be read with a meaningful vision. Contemporary architecture is constantly evolving, reflecting the changing needs of society and anticipating the challenges of the future
10.1007/978-3-031-65104-5
Keywords: (lcsh)Cultural property.; (lcsh)Buildings–Repair and reconstruction.; (lcsh)Buildings–Maintenance.; (lcsh)Digital humanities.; (lcsh)Sustainable architecture.; Cultural Heritage.; Building Repair and Maintenance.; Digital Humanities.; Sustainable Architecture/Green Buildings.